PELAKSANAAN KEBIJAKAN PAJAK SARANG BURUNG WALET KOTA PEKANBARU TAHUN 2012-2013 DALAM PERSPEKTIF OTONOMI DAERAH - Tinanto, Bherry; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru City Government to increase revenue (PAD) in accordancewith the order to build a regional autonomy impose tax Swallow's Nest which wasarranged through Pekanbaru City Regulation No. 10 of 2011 which is guided bythe Act No. 28 of 2009 on Tax and Levies. With the enactment of the TaxSwallow's Nest in the city is expected to boost revenue Pekanbaru Pekanbaru andassist in the development in the city of Pekanbaru. Swallow's Nest tax for 2 yearspassed since its implementation in 2011 until the end of December 2013 did notproduce. Swallow's Nest tax is expected to increase revenue Pekanbaru was stillvery far from the target of the tax levy itself. Departing from the abovephenomenon, the authors are interested in studying this matter with the title"Implementation of Tax Policy Swallow's Nest Pekanbaru City Year 2012-2013 inthe Perspective of Regional Autonomy".Based on the results of studies using the theory of Edward III, researchersconcluded that the Tax Policy Implementation Swallow's Nest Pekanbaru CityYear 2012-2013 in the Perspective of Regional Autonomy is not going well. Thisis due to the realization of this tax is far from the target and did not produce.Some of the causes include lack of awareness of employers to pay taxes swallow.Several factors in the implementation, such as communication between RevenueService Pekanbaru and employers do not swallow well established. Resourcessuch as the budget has not been provided to support the implementation.Employees in Pekanbaru City Revenue Service as not serious in implementing it.Keywords : Regional Autonomy, PAD, Tax, Implementation